Dual energy computed tomography in tophaceous gout. Issue 10 (9th December 2008) - Choi, H K; Al-Arfaj, A M; Eftekhari, A; Munk, P L; Shojania, K; Reid, G; Nicolaou, S
Abstract : Objective: To evaluate the potential utility of a dual energy CT (DECT) scan in assessing urate deposits among patients with tophaceous gout, and obtain computerised quantification of tophus volume in peripheral joints. Methods: 20 consecutive patients with tophaceous gout and 10 control patients with other arthritic conditions were included. DECT scans were performed using a renal stone colour-coding protocol that specifically assessed the chemical composition of the material (ie, urate coloured in red, calcium coloured in blue). An automated volumetric assessment of DECT was used to measure the volume of urate deposits in all peripheral joint areas. Results: All 20 patients with gout showed red colour-coded urate deposits on their DECT scans, whereas none of 10 controls showed urate deposits. DECT scans revealed a total of 440 areas of urate deposition in 20 patients, whereas physical examination showed 111 areas of urate deposition (mean 22 vs 6 per patient, respectively, p<0.001). Total urate volume in a given patient ranged from 0.63 cm 3 to 249.13 cm 3, with a mean of 40.20 cm 3 . Conclusions: DECT scans can produce obvious colour displays for urate deposits and help to identify subclinical tophus deposits. Furthermore, tophus volume can be measured by DECT scans through an automated volume estimation procedure.